Optimización de una torre de destilación reactiva para la producción de etilenglicol con base a una función de carácter térmico (2018)
In this article, we present the importance and application of an optimization model for the design and simulation of chemical processes, known as quadratic sequential programming (SQP), which is an extension of Lagrange multipliers assisted with Karush Kuhn Tukker conditions. (KKT). When performed by simulation, initially the models available in the Aspen Plus® simulator are discussed and the SQP model is chosen by a convergence criterion. Likewise, an analysis is made for a case study focused on the formulation of the objective function, the restrictions for the optimization system and its solution using the aforementioned process simulator. To apply the concepts, a reactive distillation tower for the production of ethylene glycol with multiple feed and a reactive zone located in the first 5 stages is taken as a case study. This is modeled in the Aspen Plus® simulator in its version 9.0. For the verification of the solution, 2 post optimization analyzes are used, the first one for the calculation of the Totalized Annual Cost (TAC), and as a second method, the response surfaces are used to find the behavior of the constraints and the objective function with respect to the independent variables of the system. The objective function is taken as the ratio of the heat of the reboiler and the bottom product, taking into account that the cost of heating the mixture is significant in the operation of the tower, which is restricted to obtain an ethylene oxide composition. In peaks of 95 % and a composition of ethylene glycol in funds greater than 90 %. As a result of the optimization, the heat used by the reboiler and by the condenser is decreased, in other words, the amount of cooling services provided by water, such as the heating ones provided by high pressure steam are minimized.